PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM LQ45 PADA BURSA EFEK INDONESIA TAHUN 2016-2019 - Ezra Oktiano Prasetja; Inayati Nuraini Dwiputri2= (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
The stock price of a company can be used to determine its success. One of the efforts made to increase the cash and capital of a company is to sell securities. Parties who have funds (investors) in making investments certainly want to maximize profits and minimize risk by conducting analysis. To analyze the ups and downs of stock prices there are 2 analytical techniques, namely technical analysis and also fundamental analysis techniques. Researchers discuss the impact of fundamental and macroeconomic factors on stock prices in this article. The study used panel data with multiple linear regression models. Here are 8 independent variables that researchers used in this study, among others, namely debt to equity ratio, return on equity, earnings per share, price earning ratio, return on assets, book value, price to book value, rupiah exchange rate while for dependent variables researchers use stock prices. The researcher obtained the data through a summary of the performance of LQ45 companies contained on the Indonesia Stock Exchange. The study's findings revealed that fundamental factors, such as return on assets and price to book value, had a significant impact on stock prices. Macroeconomic factors also influence the rise and fall of stock prices, and in this study, macroeconomic factors are represented by the rupiah's variable exchange rate (exchange rate) against the dollar.